PENEGAKAN HUKUM LINGKUNGAN TERHADAP KERUSAKAN LINGKUNGAN HIDUP - Muthmainnah, Wahyu Rasyid, Iin Lestari (FAKULTAS HUKUM UM PAREPARE, 2020)
This study aims to determine the enforcement of environmental law against environmentaldamage and the inhibiting factors in environmental law enforcement. This type of research isnormative research. Data collection techniques used were literature study. The data analysistechnique used is qualitative descriptive. The findings obtained from this study include: (1)Enforcement of environmental law on environmental uses three law enforcement instruments namelyfirstly administrative law enforcement. The second is the enforcement of criminal law, thisreiteration through three attempts, namely, Pre-emptive Actions, preventive measures and repressiveactions. Third is civil law enforcement where the lawsuit is filed through the court; (2) inhibitingfactors in environmental law enforcement are the meaning of words in the law that are difficult tounderstand and have other meanings, lack of forest police personnel, lack of facilities such asvehicles to conduct surveillance, lack of community understanding of the effects of illegal logging,and understanding of the community assume that the forest is a legacy from ancestors so that cuttingdown is not a crime.